Determining On‐Target, Off‐Target, and Copy Number Status of Transgenic Events After CRISPR/Cas9 Targeted AAVS1 Safe‐Harbor Modification of iPSCs Using Double‐Control Quantitative Copy Number PCR. Issue 1 (4th January 2023) - Schjeide, Brit‐Maren Michaud; Püschel, Gerhard Paul
Abstract: Double‐control quantitative copy number PCR (dc‐qcnPCR) is a recently described tool that can be used to quantify donor DNA insertions in genetically modified monoclonal cell lines. In conjunction with an insert‐confirmation PCR, the technique can quickly and easily identify clones containing on‐target heterozygous or homozygous donor DNA integrations and exclude off‐target insertions. The genetic manipulation of immortal cell lines is a versatile tool to elucidate cellular signaling pathways and protein functions. Despite recent advances in the precision of genetic engineering tools such as CRISPR/Cas9, transcription‐activator‐like effector nucleases (TALENs), and zinc‐finger nucleases (ZFNs), it is still essential to verify the accurate insertion of the sequence of interest (donor DNA) into the targeted genomic DNA (gDNA) locus. This precise integration into a genetic safe harbor, and exclusion of the donor DNA from functionally relevant genes, can ensure normal cellular functionality. Current methods to analyze the specificity of donor DNA insertions either are cost‐prohibitive or create dependency on manufacturers for assay design and production. The dc‐qcnPCR method is a simple, yet powerful, approach that can be prepared and carried out in any laboratory equipped with standard molecular biology supplies. Here we provide step‐by‐step instructions to prepare and perform the dc‐qcnPCR, and its companion insert‐confirmation PCR, to determine donor DNA insertion numbers in monoclonal cell lines genetically modified through CRISPR/Cas9. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Genetic modification at AAVS1 safe harbor in induced pluripotent stem cells (IMR90‐4) using CRISPR/Cas9: from plasmid design to monoclonal expansion Support Protocol 1 : Measurement of Gaussia luciferase activity to verify reporter protein functionality Support Protocol 2 : Verification of monoclonal expansion using immunofluorescence. Basic Protocol 2 : Insert‐confirmation PCR Basic Protocol 3 : Design and preparation of double‐control quantitative copy number PCR reagents and quantification of donor DNA integrations in genetically modified monoclonal cells